Competence Analysis Of Equality Education Tutors In The Non-Formal Education Unit Of Community Learning Activities (SPNF SKB) Banyuasin Regency - Rozi, Afrul; Shomedran, Shomedran (Universitas Pendidikan Indonesia, 2021)
The purpose of this study was to describe the exploration of education in the Non-formal Education Unit of Community Learning Activity Center (SPNF SKB) Banyuasin Regency, with sub-competencies covering pedagogical, personality, social, and professional competencies. This type of research is descriptive with a quantitative approach. The sampling technique used saturated sampling with a total of 36 learning residents. Data collection was carried out by means of questionnaires and documentation. The results showed that pedagogical competence was classified as high with a percentage of 81%, personality competence was classified as high with a percentage of 84%, social competence was classified as very high with a percentage of 86.30%, and personality competence was classified as high with a percentage of 80.80%.